Gender Analysis of Quranic Verses That Indicate Child Marriage - Nida Ul Husna; Putri Mega Shintia; Eni Zulaiha (al-Afkar, Journal For Islamic Studies, 2026)
Marriage will enable a person to achieve psychological and biological balance in life. One factor to consider in choosing a life partner is age. Age is crucial because it relates to psychological maturity. The impact of child marriage can cause children to experience profound trauma due to inhibiting factors such as reproductive health problems, impaired health, and domestic violence because the child is not yet ready for marriage. This type of research is qualitative and library research, so the data obtained comes from the study of relevant texts or books. This study uses a feminist interpretation approach that has the basic principles of the Qur'an regarding gender relations between men and women, in the assumption of feminist interpretation: justice (al-adalah), equality (al-musawah), appropriateness (al-ma'ruf), and deliberation (shura). Scholars of interpretation do not specify the exact age limit for marriage, but instead refer to two things: baligh (age of puberty) and rusydu (age of puberty). Baligh refers to physical maturity for men with wet dreams (ihtilam) and menstruation for women. Meanwhile, rusydu is interpreted as maturity in acting as appropriately as possible, which also means intelligence and mental stability when a child is entering the gates of adulthood.